Copper-chromium contact material and preparation method thereof
By preparing CuCr5Te0.5 alloy powder and combining prepression and gradient temperature-raising vacuum sintering technology, the problem of poor welding resistance of traditional copper-chromium contact materials is solved, and the reliability and service life of the material are significantly improved.
Patent Information
- Application Number
- CN202411524372.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-03-04
AI Technical Summary
Traditional copper-chrome contact materials may experience uneven wear and poor contact after multiple current cuts, which affects the reliability and service life of the vacuum circuit breaker, and are also poor in welding resistance.
By preparing CuCr5Te0.5 alloy powder and stirring and mixing with Cu powder and Cr powder in a certain proportion, copper chromium contact material with more uniform and refined microstructure was prepared through pre-pressure and gradient temperature-raising vacuum sintering process.
The anti-welding performance of copper-chrome contact materials is significantly improved, so that the contact materials show higher reliability and longer service life under high temperature operating conditions.
Smart Images

Figure CN119553118A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of alloy preparation, and specifically relates to a copper-chromium contact material and a preparation method thereof. Background Art
[0002] The traditional method for preparing copper-chromium contact materials is usually to directly mix Cu powder, Cr powder and Te powder. The contact material prepared by this method has more large grains and less fine dispersed phases inside, which will affect the conductivity and mechanical strength of the contact material. In practical applications, this means that the contact prepared by the contact material obtained by this method may have problems such as uneven wear and poor contact after multiple current interruptions, thereby affecting the reliability and service life of the vacuum circuit breaker. In addition, the anti-welding property of the contact material prepared by this method will also be adversely affected, because under the action of the arc, the unevenly distributed grains will lead to local overheating and aggravation of the welding phenomenon. Summary of the invention
[0003] In view of the deficiencies in the prior art, the purpose of the present application is to provide a copper-chromium contact material and a preparation method thereof. The present application can improve the resistance of the copper-chromium contact material to fusion welding, and when used in a vacuum circuit breaker, it can withstand more breaking operations.
[0004] To achieve the above objectives, this application provides the following technical solutions:
[0005] A method for preparing a copper-chromium contact material, the method comprising: preparing CuCr5Te 0.5 Alloy powder; Cu powder, Cr powder and CuCr5Te in a certain proportion 0.5 The alloy powder is stirred and mixed to obtain a composition of CuCr 30 Te 0.05 The component is CuCr 30 Te 0.05 The mixed powder is pre-pressed to obtain a composition of CuCr 30 Te 0.05 The alloy blank of the composition is CuCr 30 Te 0.05 The alloy blank is subjected to primary vacuum sintering to obtain an initial copper-chromium contact material after cooling; the initial copper-chromium contact material is subjected to re-pressing to obtain a copper-chromium contact blank; and the copper-chromium contact blank is subjected to secondary vacuum sintering to obtain a copper-chromium contact alloy.
[0006] Optionally, prepare CuCr5Te 0.5The alloy powder comprises the following steps: preparing a CuTe master alloy by vacuum induction melting of a Cu rod and a Te block; and obtaining a CuCr5Te master alloy by induction melting and inert gas atomization of the Cu rod, the CuTe master alloy and the CuCr alloy in a gas atomization furnace. 0.5 Alloy powder.
[0007] Optionally, the Cu powder, Cr powder and CuCr5Te 0.5 The mass percentages of the alloy powders are 60.5%, 29.5% and 10%.
[0008] Optionally, the stirring speed is 30-60 r / min and the stirring time is 2-7 h.
[0009] Optional, pre-pressing pressure is 500-650MPa / cm 2 , the holding time is 1-3s.
[0010] Optionally, a gradient heating method is used to heat the CuCr 30 Te 0.05 The alloy blank is subjected to primary vacuum sintering and secondary vacuum sintering.
[0011] Optionally, the temperature of the first vacuum sintering and the second vacuum sintering are both 300-1050°C.
[0012] Optional, the re-pressing pressure is 1000-1300MPa / cm 2 The holding time of re-pressing is 1-3s.
[0013] In addition, the present application also provides a copper-chromium contact material, the components of the copper-chromium contact material and the mass percentage of each component are:
[0014] Cu powder 60.5%
[0015] Cr powder 29.5%
[0016] CuCr5Te 0.5 Alloy 10%.
[0017] In addition, the present application also provides a vacuum circuit breaker, which includes a contact, and the contact is made of the copper-chromium contact material as described above.
[0018] Compared with the prior art, the beneficial effects brought about by the present application are as follows: the present application prepares the CuTe intermediate alloy in advance and mixes it with the CuCr alloy, and then undergoes an optimized pre-pressing and sintering process, so that the copper-chromium contact material prepared has a more uniform and refined microstructure, which significantly improves the anti-welding performance of the copper-chromium contact material, and makes the contact material exhibit higher reliability and longer service life under high temperature working conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 It is a schematic flow chart of a method for preparing a copper-chromium contact material provided in one embodiment of the present application;
[0020] Figure 2 This is a metallographic diagram of the contact material prepared by directly mixing Cu powder, Cr powder and Te powder;
[0021] Figure 3 is a metallographic diagram of the contact material prepared by the method;
[0022] Figure 4 CuCr5Te 0.5 Metallographic diagram of alloy powder. DETAILED DESCRIPTION
[0023] The specific embodiments of the present application will be described in detail below with reference to the accompanying drawings. Although the specific embodiments of the present application are shown in the accompanying drawings, it should be understood that the present application can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided in order to enable a more thorough understanding of the present application and to fully convey the scope of the present application to those skilled in the art.
[0024] It should be noted that certain words are used in the specification and claims to refer to specific components. Those skilled in the art should understand that technicians may use different nouns to refer to the same component. This specification and claims do not use the difference in nouns as a way to distinguish components, but use the difference in the functions of the components as the criterion for distinction. As mentioned throughout the specification and claims, "including" or "comprising" is an open term, so it should be interpreted as "including but not limited to". The subsequent description of the specification is a preferred embodiment of the implementation of the present application, but the description is based on the general principles of the specification and is not used to limit the scope of the present application. The scope of protection of the present application shall be determined by the attached claims.
[0025] To facilitate understanding of the embodiments of the present application, further explanation will be given below using specific embodiments as examples in conjunction with the accompanying drawings, and the various drawings do not constitute a limitation on the embodiments of the present application.
[0026] Figure 1 FIG. 1 is a flow chart of a method for preparing a copper-chromium contact material provided by an exemplary embodiment of the present application. Figure 1 As shown, the method includes:
[0027] S1: Preparation of CuCr5Te 0.5 Alloy powder;
[0028] In this step, firstly, a copper (Cu) rod and a tellurium (Te) block are placed in a vacuum induction furnace and heated to a certain temperature (e.g., heated to 1200° C.) under vacuum conditions to melt the copper (Cu) rod and the tellurium (Te) block and uniformly mix them, and this temperature is maintained for a certain period of time (e.g., 30 minutes) to ensure that Cu and Te fully react to form a uniform CuTe master alloy, and then cooled to room temperature to obtain a CuTe master alloy ingot; secondly, the copper (Cu) rod, the CuTe master alloy and the CuCr alloy are mixed in a gas atomization furnace, wherein the gas atomization furnace adopts The material is heated to 1400-1500°C in a gradient heating method (first the power of the gas atomization furnace is increased to 25KW, and kept warm for 2-10 minutes; then increased to 35KW, and kept warm for 2-10 minutes; and finally increased to 45KW) until it melts, and a high-pressure inert gas (such as argon) is introduced to atomize the melted material (the atomization pressure can be set to 0.5-2MPa). The inert gas is sprayed at high speed through the nozzle of the gas atomization furnace to disperse the molten metal in the gas atomization furnace into fine droplets, and CuCr5Te is obtained after cooling and solidification. 0.5 The alloy powder comprises about 5% by mass of chromium (Cr), about 0.05% by mass of tellurium (Te), and the remainder is copper (Cu).
[0029] Figure 4 CuCr5Te 0.5 The metallographic diagram of the alloy powder shows that the CuCr5Te 0.5 In the alloy powder, the content of Cr is 4.31wt% and the content of O is 0.064wt% (indicating that CuCr5Te 0.5 The alloy powder contains less oxide impurities, which is beneficial to maintaining good electrical conductivity and mechanical properties of the material. The N content is 0.0013wt% and the Te content is 0.45wt%. In addition, CuCr5Te 0.5 The alloy powder is spherical in shape. Spherical particles have a smaller actual contact area than irregularly shaped particles. When the surfaces of two materials come into contact with each other under high temperature conditions, the smaller contact area reduces the direct physical connection between the two, thereby reducing the risk of welding. In addition, the structure formed by the accumulation of spherical particles often has a more ideal porosity. Appropriate pores can not only reduce weight, but also serve as a buffer zone, absorb part of the heat and provide a path for gas escape, thereby preventing adhesion caused by overheating. Furthermore, since there are certain gaps between spherical particles, these gaps help dissipate heat and can keep the overall temperature of the material at a lower level, which is beneficial to prevent overheating and subsequent welding.
[0030] S2: Cu powder, Cr powder and CuCr5Te 0.5The alloy powders were mixed in a double-roll screw mixer at a ratio of 60.5%, 29.5% and 10%, with a stirring speed of 30 r / min and a stirring time of 2 h. The composition obtained after stirring was CuCr 30 Te 0.05 Mixed powder;
[0031] In this step, the copper powder is electrolytic copper powder with a purity of 99.9% and a particle size of -200 mesh; the chromium powder is prepared by aluminothermic method or liquid nitrogen low-temperature cold brittle method, or chromium is directly extracted from a chromium salt solution by electrolysis and made into powder with a particle size of -200 to +400 mesh; CuCr5Te 0.5 The alloy powder is a gas-chemical alloy powder (ie, the mass percentage of Cr is 5%, the mass percentage of Te is 0.5%, and the balance is Cu).
[0032] It should be noted that Cu powder, Cr powder and CuCr5Te 0.5 The proportion of alloy powder is calculated based on Cr content of 30wt%, Te content of 0.05wt%, and the balance of copper; specifically, first calculate 100g of CuCr 30 Te0. 05 The mixed powder requires 0.05g of Te, 30g of Cr, and 69.95g of Cu. Based on 0.05g of Te, it is calculated that CuCr5Te is needed. 0.5 The weight is 10g (of which 10g of CuCr5Te 0.5 The alloy powder contains 0.05g Te, 0.5g Cr, and 9.45g Cu), except CuCr5Te 0.5 The alloy powder contains Cu and Cr, and 60.5g of Cu powder is needed (69.95g-9.45g=60.5g). Similarly, 29.5g of Cr powder is needed (30g-0.5g=29.5g). Therefore, the Cu powder, Cr powder and CuCr5Te of CuCr30Te0.05 are 0.5 The ratio is 60.5%, 29.5% and 10%.
[0033] S3: The composition is CuCr 30 Te 0.05 The mixed powder is pre-pressed on a dry powder automatic forming hydraulic press with a pre-pressing pressure of 500MPa / cm 3 , the pre-pressing time is 1s, and the pre-pressing density is controlled at 6.8g / cm 3 , the composition after pre-pressing is CuCr 30 Te 0.05 Alloy body;
[0034] S4: The composition is CuCr 30 Te 0.05The alloy blank is placed in a vacuum sintering furnace and subjected to initial vacuum sintering by a gradient heating method, and the initial copper-chromium contact material is obtained after cooling;
[0035] In this step, during the initial sintering process, the starting temperature of the vacuum sintering furnace is set to room temperature. The temperature is first increased from room temperature to 300°C at a rate of 2°C / min, and kept warm for 2 hours; then the temperature is increased from 300°C to 500°C at a rate of 3°C / min, and kept warm for 2 hours; then the temperature is increased from 500°C to 800°C at a rate of 5°C / min, and kept warm for 3 hours. The product is then cooled to 60°C and taken out of the furnace.
[0036] S5: The initial copper-chromium contact material is re-pressed on an automatic forming hydraulic press, and the re-pressing pressure is 1000 MPa / cm 2 , holding time 1s, after re-pressing, the copper-chromium contact blank is obtained;
[0037] S6: placing the copper-chromium contact blank in a vacuum sintering furnace, and performing secondary vacuum sintering in a gradient temperature increase manner to obtain a powder metallurgy copper-chromium contact alloy with high resistance to fusion welding.
[0038] In this step, the secondary sintering adopts the same gradient temperature rise sintering method as the primary sintering, which will not be described again here.
[0039] It should be noted that in the conventional method, Cu powder, Cr powder and Te powder are usually mixed to prepare CuCrTe mixed powder contacts. Cu powder and Te powder are solid-phase sintered, and Cu and Te cannot fully react to form Cu2Te alloy phase. The effect of improving the resistance of the contact to fusion welding by adding Te is not good. In this embodiment, by preparing the CuTe master alloy in advance, it is possible to ensure that the Te element is stably fixed in the CuTe master alloy, thereby reducing the volatilization loss of the Te element in the subsequent smelting process, making the Te content in the CuCr5Te0.5 alloy powder more accurate and helpful to form a stable and uniform CuTe brittle phase. In addition, the present embodiment adopts CuCr alloy. When the CuTe master alloy is adopted, the CuTe brittle phase formed on the CuCr interface can be more stably and evenly distributed inside the CuTe master alloy. This brittle phase makes the finally prepared copper-chromium contact easier to break from the interface and the matrix under high temperature working conditions. When the arc or thermal stress acts, these brittle phases can promote the timely peeling of the surface melted material, thereby reducing or preventing the occurrence of fusion welding. Directly adding chromium (Cr) blocks and tellurium (Te) blocks will result in uneven distribution of Te elements in the alloy, which will affect the formation of CuTe brittle phases, resulting in insufficient or uneven distribution of CuTe brittle phases, thereby affecting the anti-welding performance of the contact material. Furthermore, the CuTe master alloy and the CuCr alloy can be completely melted at a lower temperature, thereby reducing the time required for the entire smelting process, thereby improving the preparation efficiency of the copper-chromium contact material.
[0040] In another exemplary embodiment, the present application also provides a method for preparing a copper-chromium contact material, the method comprising:
[0041] S10: Preparation of CuCr5Te 05 Alloy powder;
[0042] S20: Cu powder, Cr powder and CuCr5Te 0.5 The alloy powders were mixed in a double-roll screw mixer at a ratio of 60.5%, 29.5% and 10%, with a stirring speed of 50 r / min and a stirring time of 5 h. The composition obtained after stirring was CuCr 30 Te 0.05 Mixed powder;
[0043] S30: The component is CuCr 30 Te 0.05 The mixed powder is pre-pressed on a dry powder automatic forming hydraulic press with a pre-pressing pressure of 600MPa / cm 2 , the pre-pressing time is 2s, and the pre-pressing density is controlled at 7.2g / cm 3 After pre-pressing, the composition is CuCr 30 Te0.05 Alloy body;
[0044] S40: The component is CuCr 30 Te 0.05 The alloy blank is placed in a vacuum sintering furnace and subjected to initial vacuum sintering by a gradient heating method, and the initial copper-chromium contact material is obtained after cooling;
[0045] In this step, during the initial sintering process, the starting temperature of the vacuum sintering furnace is set to room temperature, firstly, the temperature is increased from room temperature to 300°C at a rate of 2°C / min, and kept at this temperature for 2 hours; then the temperature is increased from 300°C to 500°C at a rate of 1°C / min, and kept at this temperature for 2 hours; then the temperature is further increased from 500°C to 950°C at a rate of 2.5°C / min, and kept at this temperature for 4 hours, and then the furnace is cooled to 60°C and taken out of the furnace.
[0046] S50: The initial copper-chromium contact material is re-pressed on an automatic forming hydraulic press, and the re-pressing pressure is 1150 MPa / cm 2 , holding time is 2s, and after re-pressing, a copper-chromium contact blank is obtained;
[0047] S60: placing the copper-chromium contact blank in a vacuum sintering furnace, and performing secondary vacuum sintering in a gradient temperature increase manner to obtain a powder metallurgy copper-chromium contact alloy with high resistance to fusion welding.
[0048] In this step, the secondary sintering adopts the same gradient temperature rise sintering method as the primary sintering, which will not be described again here.
[0049] In another embodiment, the present application also provides a method for preparing a copper-chromium contact material, the method comprising:
[0050] S100: Preparation of CuCr5Te 0.5 Alloy powder;
[0051] S200: Cu powder, Cr powder and CuCr5Te 0.5 The alloy powders were mixed in a double-roll screw mixer at a ratio of 60.5%, 29.5% and 10%, with a stirring speed of 60 r / min and a stirring time of 7 h. The composition obtained after stirring was CuCr 30 Te 0.05 Mixed powder;
[0052] S300: for the component CuCr 30 Te 0.05 The mixed powder is pre-pressed on a dry powder automatic forming hydraulic press with a pre-pressing pressure of 650MPa / cm 2 , the pre-pressing time is 3s, and the pre-pressing density is controlled at 7.8g / cm 3 After pre-pressing, the composition is CuCr30 Te 0.05 Alloy body;
[0053] S400: The component is CuCr 30 Te 0.05 The alloy blank is placed in a vacuum sintering furnace and subjected to initial vacuum sintering by a gradient heating method, and the initial copper-chromium contact material is obtained after cooling;
[0054] In this step, during the initial sintering process, the starting temperature of the vacuum sintering furnace is set to room temperature, firstly, the temperature is increased from room temperature to 300°C at a rate of 2°C / min, and kept at this temperature for 2 hours; then the temperature is increased from 300°C to 500°C at a rate of 1°C / min, and kept at this temperature for 2 hours; then the temperature is further increased from 500°C to 1050°C at a rate of 2.5°C / min, and kept at this temperature for 5 hours, and then the furnace is cooled to 60°C and taken out of the furnace.
[0055] S500: The initial copper-chromium contact material is re-pressed on an automatic forming hydraulic press, and the re-pressing pressure is 1300 MPa / cm 2 , holding time is 3s, and after re-pressing, a copper-chromium contact blank is obtained;
[0056] S600: placing the copper-chromium contact blank in a vacuum sintering furnace, and performing secondary vacuum sintering in a gradient temperature increase manner to obtain a powder metallurgy copper-chromium contact alloy with high resistance to fusion welding.
[0057] In this step, the secondary sintering adopts the same gradient temperature rise sintering method as the primary sintering, which will not be described again here.
[0058] In the above embodiment, it has been verified by experiments that if the pre-compression pressure is less than 500 MPa / cm 2 , which will lead to insufficient bonding force of the mixed powder, insufficient density of the alloy blank and too many voids inside, which will cause deformation or cracking during the subsequent sintering process, resulting in loose contact materials, high porosity and decreased mechanical properties. High porosity and low density will reduce the overall strength and thermal stability of the contact materials, making it more likely for the contact materials to weld under high temperature working conditions. On the contrary, if the preloading pressure is greater than 650MPa / cm 2, it will lead to excessive extrusion between the mixed powder particles, resulting in excessive density in local areas of the alloy blank, and even the formation of hard lumps, which will easily cause cracks during sintering or use. The cracks will cause the ablation resistance of the contact material to decrease, and then lead to failure of the contact material and welding. In addition, it has been verified by experiments that if the pre-pressing time is less than 1s, the mixed powder will not have enough time to be fully compressed and evenly distributed, which will lead to uneven internal structure and high porosity of the contact material. The uneven internal structure and high porosity will cause the contact material to easily overheat locally at high temperatures, increasing the risk of welding. On the contrary, if the pre-pressing time is greater than 3s, the mixed powder will be over-compacted, making some areas too tight, and even causing local stress concentration, increasing the risk of fracture of the alloy blank during sintering, and thus weakening the resistance of the contact material to welding.
[0059] In summary, the preload pressure is set to 500-650MPa / cm 2 , and setting the pre-pressing time to 1-3s can prevent the mixed powder from being locally too dense or too sparse to achieve a more ideal density, which is helpful for CuCr 30 Te 0.05 The internal particles of the alloy blank are closely arranged, reducing the porosity, thereby improving the resistance of the contact material to welding. In addition, the pre-pressing density is maintained at 6.8-7.8g / cm 3 The porosity in the mixed powder can be effectively controlled. Too low density will lead to too many pores, causing uneven shrinkage of the alloy body during sintering, which will easily cause cracks or defects; while too high density will cause the local area of the mixed powder to be too dense, which will also affect the uniformity and consistency of the final product.
[0060] In summary, the present application has been verified by experiments that when the pre-compression pressure is set to 500-650MPa / cm 2 , and the pre-pressing time is 1-3s. This combination of process parameters can effectively control the pre-pressing density of the alloy blank to 6.8-7.8g / cm during the preparation of copper-chromium contact materials. 3 range, thereby improving the anti-welding performance of the contact material.
[0061] In the above embodiment, the sintering temperature of the primary vacuum sintering and the secondary vacuum sintering is set to 300-1050°C. It has been verified by experiments that if the sintering temperature is less than 300°C, CuCr 30 Te 0.05The diffusion and rearrangement process between particles in the alloy blank or copper-chromium contact blank will become very slow, making it difficult for the copper-chromium contact material to achieve sufficient density. In addition, due to the lack of sufficient heat energy to promote material flow and fill pores, the porosity will be too high. Low density and high porosity will increase resistance, thereby causing local overheating and promoting the occurrence of welding. On the contrary, if the sintering temperature is greater than 1050°C, CuCr 30 Te 0.05 The particles in the alloy blank or copper-chromium contact blank may be over-melted or over-diffused, resulting in grain growth, which in turn reduces the hardness and wear resistance of the copper-chromium contact material. The reduced hardness and wear resistance will make the contact material more susceptible to wear and deformation under high-temperature working conditions, thereby increasing the possibility of fusion welding. In addition, if the temperature is too high, due to the different atomic mobility of copper (Cu), chromium (Cr) and tellurium (Te), some elements may move to new positions faster than other elements. This uneven diffusion will cause certain areas inside the alloy to be enriched with a certain element, while other areas are relatively poor. For example, chromium may be concentrated at certain grain boundaries, while copper may be enriched inside the grains, resulting in composition segregation. Composition segregation will lead to the formation of different phase structures. If a certain area is enriched with too much of a certain element, a second phase or impurity phase different from the matrix may be formed. For example, in a copper-chromium alloy, excess chromium may form a hard Cr 23 C6 carbides, the presence of these carbides will change the mechanical properties of copper-chromium contact materials, such as hardness and toughness. In addition, component segregation will also lead to a decrease in the mechanical properties of copper-chromium contact materials. For example, the segregation area may become a crack initiation point, thereby reducing the tensile strength and fatigue life of the copper-chromium contact material, which not only affects the overall strength of the contact material, but also increases its risk of fracture and welding at high temperatures.
[0062] In summary, the present application sets the sintering temperature between 300-1050°C so that CuCr 30 Te 0.05 The diffusion and rearrangement process between particles in the alloy blank or copper-chromium contact blank can be carried out effectively to ensure that the contact material reaches sufficient density, while avoiding the problems of excessive grain growth and composition segregation, thereby significantly improving the anti-welding performance of the contact material.
[0063] Figure 2 This is a metallographic diagram of the contact material prepared by directly mixing Cu powder, Cr powder and Te powder; Figure 3 This is a metallographic diagram of the contact material prepared by this method. Figure 2 In the process, Cu powder, Cr powder and Te powder are directly mixed and sintered. Since the Cr particles are relatively large and unevenly distributed, Figure 2A larger matrix copper phase-enriched area was observed in the contact material. This structure will lead to more large grains and fewer fine dispersed phases inside the contact material, thus affecting the overall performance of the contact material. Figure 3 In this application, by using the pre-prepared CuCr5Te 0.5 The alloy powder is then mixed with Cu powder and Cr powder, so that the contact material finally prepared has a more uniform and refined microstructure. Figure 3 It can be seen that there are many fine chromium (Gr) phases in the copper matrix. These fine chromium particles are evenly distributed in the copper matrix, forming a more compact and uniform microstructure. Chromium is a high melting point, corrosion-resistant element. Its fine particles are evenly distributed in the copper matrix, forming a protective layer that can improve the thermal conductivity of the contact material and increase the mechanical strength, and can reduce the direct impact of the arc on the copper matrix, thereby improving the overall ablation resistance of the contact material.
[0064] Furthermore, the present application tests various properties of the copper-chromium contact material prepared by the present method and the copper-chromium contact material prepared by the traditional method, and the test results are shown in Table 1:
[0065] Table 1
[0066]
[0067] As can be seen from Table 1, the copper-chromium contact material prepared by the present method can withstand 60 breaking operations of high-frequency breaking current, while the copper-chromium contact material prepared by the traditional method can only withstand 50 breaking operations, which means that under the same working conditions, the durability of the contact material prepared by the present method is enhanced, and the wear of the contact under the action of high-frequency breaking current is reduced. The copper-chromium contact material prepared by the present method is used to prepare the contact of the vacuum circuit breaker, which can improve the reliability of the vacuum circuit breaker. For the power system, a reliable circuit breaker means that the stability and continuous power supply capacity of the power grid are guaranteed.
[0068] Only the copper-chromium contact material prepared by this method passed the T100a test (an electrical performance test, a test of thermal stability and electrical life of contact materials), indicating that the copper-chromium contact material prepared by this method has better long-term operation stability and anti-welding performance, and can better withstand high temperature and high current shocks without welding, thereby ensuring that the vacuum circuit breaker can still work normally under extreme conditions.
[0069] The density of the copper-chromium contact material prepared by the method is 96.6%, while the density of the copper-chromium contact material prepared by the traditional method reaches 98.5%, and the lower density helps to improve the resistance to fusion welding. Therefore, the material of the method has a better performance in resistance to fusion welding due to its relatively low density.
[0070] The hardness of the copper-chromium contact material prepared by this method is 80HV, which is lower than the 85HV of the copper-chromium contact material prepared by the traditional method. The lower hardness means that the contact material is more likely to deform rather than break, thereby reducing the possibility of welding due to local overheating.
[0071] The tensile strength of the copper-chromium contact material prepared by the method is 260 MPa, which is also lower than the tensile strength of 300 MPa of the copper-chromium contact material prepared by the traditional method. The lower the tensile strength, the more conducive it is to reducing the risk of fusion welding.
[0072] In summary, it can be seen from the data in Table 1 that compared with the contact material prepared by the traditional method, the copper-chromium contact material prepared by the present method shows better comprehensive performance in various performance tests, especially in terms of resistance to welding. This will be directly reflected in the service life of the vacuum circuit breaker. A more durable contact material means that the maintenance interval of the vacuum circuit breaker can be extended, which can reduce the downtime and maintenance costs caused by replacing the contacts.
[0073] The above are only preferred embodiments of the present application, and are not intended to limit the patent scope of the present application. Any equivalent structure or equivalent process transformation made using the contents of the present application specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present application.
Claims
1. A method for preparing a copper-chromium contact material, characterized in that: The method comprises: Preparation of CuCr5Te 0.5 Alloy powder; Cu powder, Cr powder and CuCr5Te 0.5 The alloy powder is stirred and mixed to obtain a composition of CuCr 30 Te 0.05 Mixed powder; For the component CuCr 30 Te 0.05 The mixed powder is pre-pressed to obtain a composition of CuCr 30 Te 0.05 Alloy body; For the component CuCr 30 Te 0.05 The alloy blank is subjected to initial vacuum sintering, and the initial copper-chromium contact material is obtained after cooling; Re-pressing the initial copper-chromium contact material to obtain a copper-chromium contact blank; The copper-chromium contact blank is subjected to secondary vacuum sintering to obtain a copper-chromium contact alloy.
2. The preparation method according to claim 1, characterized in that: Preparation of CuCr5Te 0.5 The alloy powder comprises the following steps: The CuTe master alloy is prepared by vacuum induction melting of Cu rods and Te blocks; CuCr5Te was obtained by induction melting and inert gas atomization of Cu rod, CuTe master alloy and CuCr alloy in a gas atomization furnace. 0.5 Alloy powder.
3. The preparation method according to claim 1, characterized in that: The Cu powder, Cr powder and CuCr5Te 0.5 The mass percentages of the alloy powders are 60.5%, 29.5% and 10%.
4. The preparation method according to claim 1, characterized in that: The stirring speed is 30-60r / min and the stirring time is 2-7h.
5. The preparation method according to claim 1, characterized in that: Pre-pressing pressure is 500-650MPa / cm 2 , the holding time is 1-3s.
6. The preparation method according to claim 1, characterized in that: The composition of CuCr was tested by gradient heating. 30 Te 005 The alloy blank is subjected to primary vacuum sintering and secondary vacuum sintering.
7. The preparation method according to claim 1, characterized in that: The temperature of the first vacuum sintering and the second vacuum sintering is 300-1050°C.
8. The preparation method according to claim 1, characterized in that: The re-pressing pressure is 1000-1300MPa / cm 2 The holding time of re-pressing is 1-3s.
9. A copper-chromium contact material, characterized in that: The components of the copper-chromium contact material and the mass percentage of each component are: Cu powder 60.5% Cr powder 29.5% CuCr5Te 0.5 Alloy 10%.
10. A vacuum circuit breaker, characterized in that: The vacuum circuit breaker comprises a contact, and the contact is made of the copper-chromium contact material according to claim 9.